Desiccant components and applications thereof

CN122974267APending Publication Date: 2026-10-27江苏新劢德医疗器械科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611316788.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本申请提供一种干燥剂部件及其应用,目的是为了解决现有干燥剂部件在结构强度和吸湿性能之间难以兼顾的问题

Benefits of technology

(1)通过将A型沸石分子筛与聚烯烃、亲水性聚醚二醇配合,相较于仅含分子筛和粘结剂的二元体系,在保持结构强度的同时显著提高了吸湿速率和吸湿量,实现了吸湿性能和结构强度的良好平衡;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a desiccant component and application thereof, and belongs to the technical field of desiccants. The desiccant component comprises a type A zeolite molecular sieve, polyolefin and hydrophilic polyether glycol, wherein the proportion of the polyolefin is 31%-34% according to the total weight of the desiccant component, and the proportion of the hydrophilic polyether glycol is 1%-4%. The desiccant component takes the type A zeolite molecular sieve as a main moisture absorption component, takes the polyolefin as a binder to provide structural strength, and takes the hydrophilic polyether glycol as a moisture absorption promoter, so that the moisture absorption rate and the moisture absorption amount of the desiccant component can be significantly improved, and the use requirement of adaptation to different humidity environments can be realized by adjusting the content of the hydrophilic polyether glycol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of desiccant component technology, specifically to a desiccant component and its application. Background Technology

[0002] Desiccants are widely used in electronic device packaging, food packaging, and pharmaceutical packaging to absorb moisture from the environment and protect products from moisture damage. Common desiccants include silica gel, calcium chloride, and molecular sieves. Among them, molecular sieve desiccants play an important role in industrial applications due to their uniform pore size and strong adsorption capacity.

[0003] Molecular sieves are crystalline aluminosilicates with a uniformly distributed pore structure and a large internal surface area, enabling them to capture water molecules through physical adsorption. Molecular sieves have uniform pore size, exhibit high adsorption selectivity for water molecules, and maintain strong adsorption capacity even at low relative humidity. However, molecular sieve powder itself lacks structural strength and cannot be directly molded into desiccant components with specific shapes and sizes.

[0004] Existing molecular sieve desiccants are typically prepared by molding a combination of molecular sieves and binders. However, while this binary system of desiccants containing only molecular sieves and binders possesses a certain moisture absorption capacity and can achieve structural strength through molding, its moisture absorption rate and amount still have room for improvement. To enhance moisture absorption performance, methods such as increasing the molecular sieve content or changing the molecular sieve type are commonly employed; however, excessively high molecular sieve content can affect the structural strength of the desiccant components and easily lead to pulverization, while changing the molecular sieve type may affect adsorption selectivity.

[0005] Therefore, a desiccant that can maintain good structural strength and has excellent moisture absorption properties is needed. Summary of the Invention

[0006] This application provides a desiccant component and its application, aiming to solve the problem that existing desiccant components are difficult to balance between structural strength and moisture absorption performance.

[0007] The desiccant component provided in this application includes type A zeolite molecular sieve, polyolefin, and hydrophilic polyether glycol, wherein, based on the total weight of the desiccant component, the proportion of polyolefin is 31% to 34%, and the proportion of hydrophilic polyether glycol is 1% to 4%.

[0008] In this application, type A zeolite molecular sieve serves as the main moisture-absorbing component, providing the core moisture-absorbing capacity of the desiccant component; polyolefin acts as a binder, enabling the desiccant component to be molded and possess structural strength; hydrophilic polyether glycol, as a moisture absorption promoter, contains a large number of hydroxyl groups and ether bonds, exhibiting strong hydrophilicity, and can rapidly adsorb water molecules from the environment and transfer them to the molecular sieve channels, thereby significantly improving the moisture absorption rate and amount of the desiccant component. Furthermore, by adjusting the content of hydrophilic polyether glycol, desiccant components with different formulations can be provided for different humidity environments: in environments with a relative humidity not exceeding 80%RH, a formulation with a higher proportion of hydrophilic polyether glycol can achieve a faster moisture absorption rate and a larger moisture absorption amount; in high-humidity environments with a relative humidity of 80%~90%RH, a formulation with a lower proportion of hydrophilic polyether glycol can maintain good moisture absorption performance while avoiding the generation of surface exudates; thus, it can adapt to the usage requirements of different humidity environments.

[0009] Specifically, the hydrophilic polyether glycol molecule contains numerous hydroxyl groups and ether bonds. The hydroxyl groups can form hydrogen bonds with water molecules, allowing water molecules to be rapidly adsorbed onto the surface of the hydrophilic polyether glycol molecular chain. The oxygen atoms in the ether bonds have strong electronegativity, enabling dipole-dipole interactions with water molecules, further enhancing the adsorption capacity. Driven by the concentration gradient, water molecules adsorbed on the surface of the hydrophilic polyether glycol molecular chain migrate towards the interface between the hydrophilic polyether glycol and the molecular sieve, and then enter the pores of the molecular sieve where they are firmly adsorbed. This mass transfer process allows water molecules to not only be directly adsorbed through the molecular sieve on the surface of the desiccant component, but also indirectly reach the internal molecular sieve pores through conduction via the hydrophilic polyether glycol molecular chain. This significantly increases the effective moisture absorption area of ​​the desiccant component, improving the moisture absorption rate and saturated moisture absorption capacity.

[0010] In some embodiments of this application, the type A zeolite molecular sieve is selected from one or more of 4A molecular sieve (MS(4A)), 3A molecular sieve, and 5A molecular sieve. Among them, the pore size of 4A molecular sieve is about 0.4 nm, which matches the dynamic diameter of water molecules and has high adsorption selectivity for water molecules, making it a preferred option.

[0011] In some embodiments of this application, the proportion of type A zeolite molecular sieve is 60% to 70%, preferably 65%. When the proportion of type A zeolite molecular sieve is less than 60%, the overall moisture absorption capacity of the desiccant component is insufficient; when it is higher than 70%, the structural strength of the desiccant component decreases, making it prone to pulverization. When the proportion of type A zeolite molecular sieve is 65%, a better balance can be achieved between moisture absorption capacity and structural strength in the desiccant component. The crystal framework of type A zeolite molecular sieve is composed of alternating silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra, forming a three-dimensional interconnected pore system with a pore size of approximately 0.3 to 0.5 nm. Among them, the pore size of 4A molecular sieve is approximately 0.4 nm, which matches the dynamic diameter of water molecules (approximately 0.265 nm), allowing water molecules to enter the pores while repelling other larger molecules, thus exhibiting high adsorption selectivity. The moisture absorption process of type A zeolite molecular sieve is physical adsorption, without involving the formation and breaking of chemical bonds. After adsorbing water molecules, the crystal structure of the molecular sieve is not changed, therefore it can be regenerated and reused after heating desorption.

[0012] In some embodiments of this application, the polyolefin is selected from one or more of polypropylene (PP), high-density polyethylene (HDPE), low-density polyethylene (LDPE), and linear low-density polyethylene (LLDPE). Among them, polypropylene has high crystallinity and good water resistance, and as a binder, it can give the desiccant component high structural strength and low water absorption, which is a preferred option.

[0013] In some embodiments of this application, the hydrophilic polyether glycol is selected from one or more of polyethylene glycol (PEG), polypropylene glycol (PPG), ethylene glycol (EG), diethylene glycol (DEG), and triethylene glycol (TEG). Among them, polyethylene glycol has a suitable molecular weight and good hydrophilicity, and has good compatibility with polyolefins, making it a preferred option.

[0014] In some embodiments of this application, when the desiccant component is used in an environment with a relative humidity not exceeding 80% RH, the proportion of polyolefin is 31% to 33%, and the proportion of hydrophilic polyether glycol is 2% to 4%. Within this range, the desiccant component has a faster moisture absorption rate and a larger moisture absorption capacity, and does not produce surface exudates. As the proportion of hydrophilic polyether glycol increases, the proportion of polyolefin decreases accordingly.

[0015] In some embodiments of this application, when the desiccant component is used in a high-humidity environment with a relative humidity of 80% to 90% RH, the proportion of polyolefin is 33% to 34%, and the proportion of hydrophilic polyether glycol is 1% to 2%, that is, the proportion of hydrophilic polyether glycol does not exceed 2%. Within this range, the desiccant component has good moisture absorption performance for 7 days and does not produce surface precipitates. When the proportion of hydrophilic polyether glycol exceeds 2%, surface precipitates will form on the desiccant component within several days to two weeks in a high-humidity environment, affecting the performance. The reason for the formation of surface precipitates is that after the hydrophilic polyether glycol becomes saturated with water, the water overflows and carries away the molecular sieve powder, resulting in an oily precipitate on the surface of the desiccant component. Specifically, the mechanism of surface precipitate formation is that the hydrophilic polyether glycol exists in a dispersed state in the polyolefin matrix. When the humidity in the environment is high, the hydrophilic polyether glycol continuously adsorbs water molecules, and its volume gradually expands. When the water absorption exceeds the capacity of the hydrophilic polyether glycol within the polyolefin matrix, the absorbed hydrophilic polyether glycol overflows from the surface of the desiccant component, carrying some molecular sieve powder with it, forming an oily precipitate. The appearance of this precipitate affects the desiccant component's appearance and can cause it to become sticky and loosely structured, reducing its moisture absorption performance and lifespan. Therefore, in high-humidity environments, the proportion of hydrophilic polyether glycol should be controlled below 2% to delay or prevent the formation of surface precipitates.

[0016] In some embodiments of this application, the desiccant component is in the form of any one of granules, flakes, or columns.

[0017] In some embodiments of this application, the desiccant component can be sheet-like, columnar, button-like, horseshoe-shaped, etc. The desiccant component may have through holes for easy fixing inside containers such as drying boxes; the through holes can be round, elliptical, triangular, or other shaped. The surface of the desiccant component can be recessed inward to form grooves, increasing the moisture absorption area and improving the moisture absorption rate; the grooves can be fan-shaped, straight, curved, or other shaped; the number of grooves can be multiple.

[0018] In some embodiments of this application, the desiccant component is prepared by mixing type A zeolite molecular sieve, polyolefin, and hydrophilic polyether glycol in a certain proportion, followed by melt blending, and then extrusion granulation or injection molding. Specifically, the polyolefin can be heated and melted first, then type A zeolite molecular sieve and hydrophilic polyether glycol can be added and mixed evenly, and finally extruded and granulated or injection molded into the desired shape.

[0019] The desiccant component provided in this application can be applied to fields such as electronic device packaging, food packaging, and pharmaceutical packaging. The formulation can be selected according to the humidity conditions of the environment: for environments with a relative humidity not exceeding 80% RH, a formulation with 31%~33% polyolefin and 2%~4% hydrophilic polyether glycol is used; for high-humidity environments with a relative humidity of 80%~90% RH, a formulation with 33%~34% polyolefin and no more than 2% hydrophilic polyether glycol is used. Specifically, the desiccant component of this application can be divided into a first type and a second type: the first type of desiccant component has a hydrophilic polyether glycol content of no more than 2%, is suitable for high-humidity environments with a relative humidity of 80%~90% RH, and features fast moisture absorption rate, high moisture absorption capacity, and low surface exudation; the second type of desiccant component has a hydrophilic polyether glycol content of 2%~4%, is suitable for environments with a relative humidity not exceeding 80% RH, and features even faster moisture absorption rate, higher moisture absorption capacity, and low surface exudation.

[0020] Compared with the prior art, the beneficial effects of this application are as follows: (1) By combining type A zeolite molecular sieve with polyolefin and hydrophilic polyether glycol, compared with the binary system containing only molecular sieve and binder, the moisture absorption rate and moisture absorption capacity are significantly improved while maintaining structural strength, thus achieving a good balance between moisture absorption performance and structural strength. (2) By adjusting the content of hydrophilic polyether glycol, the moisture absorption rate and amount of the desiccant component can be controlled to meet the usage requirements of different humidity environments. (3) In particular, in a high humidity environment with a relative humidity of 80%~90%RH, a formulation with a hydrophilic polyether diol content of no more than 2% can maintain good moisture absorption performance while avoiding the generation of surface exudates. (4) In an environment with a relative humidity not exceeding 80%RH, a formulation with a hydrophilic polyether glycol content of 2% to 4% can achieve a faster moisture absorption rate and a larger saturated moisture absorption capacity, and is less prone to surface exudation. For specific experimental data on the above effects, please refer to the examples and comparative examples below.

[0021] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this application. Detailed Implementation

[0022] The present application will be further described below through specific embodiments. It should be understood that the embodiments are only used to illustrate the technical solutions of the present application, and are not intended to limit the scope of protection of the present application. In each embodiment, the proportion of each component is based on the total weight of the desiccant component; the 4A molecular sieve (MS(4A)) was purchased from public channels, and the polypropylene (PP) and polyethylene glycol (PEG) were both commercially available industrial-grade products.

[0023] During the preparation of the desiccant component, the melt blending temperature can be set above the melting point of the polyolefin, for example, 170℃~200℃, to ensure that the polyolefin is fully melted and uniformly mixed with other components. The mixing time can be 5~15 minutes to ensure that the molecular sieve powder and hydrophilic polyether glycol are uniformly dispersed in the polyolefin melt. During extrusion granulation, the temperature of each section of the extruder can be set to 170℃~200℃, and the screw speed can be adjusted according to the equipment specifications. During injection molding, the die temperature can be set from room temperature to 60℃, and the injection pressure can be determined according to the shape and size of the desiccant component. The prepared desiccant component can be tested for performance after cooling to room temperature.

[0024] Moisture absorption test method: Place the desiccant component sample in a constant temperature and humidity environment, weigh it periodically, and calculate the moisture absorption (unit: mg / PCS, i.e., the moisture absorption weight gain of each sample) and the moisture absorption ratio (moisture absorption / initial sample weight × 100%). Test conditions include 25℃ / 50%RH, 25℃ / 90%RH, and 22℃ / 80%RH.

[0025] Method for determining surface precipitates: Observe whether grease-like precipitates appear on the surface of the desiccant component sample and record the precipitation time. The precipitate is a mixture of water that overflows after the hydrophilic polyether glycol becomes saturated with water and molecular sieve powder (i.e., the precipitated "grease-like precipitate" is essentially a mixture of water and molecular sieve powder). Once surface precipitates appear, the moisture absorption data measured afterward is not accurate enough and has limited reference value.

[0026] During testing, the desiccant component sample is placed in a constant temperature and humidity test chamber. The temperature and relative humidity of the chamber can be adjusted according to the set test conditions. The desiccant component sample can be placed on a porous shelf inside the test chamber to ensure air circulation around the sample. For weighing, the desiccant component sample is removed from the test chamber and quickly weighed and recorded using an electronic balance (accuracy up to 0.1 mg). The weighing process should be completed within 30 seconds to minimize the impact of environmental changes on the test results.

[0027] Example 1: Preparation of desiccant component sample S1. Following a formulation of 65% 4A molecular sieve (MS(4A)), 34% polypropylene (PP), and 1% polyethylene glycol (PEG), the components were mixed, melt-blended, and extruded to obtain sample S1, which has a columnar structure with through holes and grooves. Sample S1 was subjected to moisture absorption tests at 25℃ / 50%RH and 25℃ / 90%RH, respectively.

[0028] Example 1 Test Results: At 25℃ / 50%RH, the 7-day moisture absorption was 159.7 mg / PCS, with a moisture absorption ratio of 1.81% (saturation is reached in approximately 11-12 weeks under these conditions). At 25℃ / 90%RH, the 24-hour moisture absorption was 168 mg / PCS, with a moisture absorption ratio of 1.90%; the 7-day moisture absorption was 479.8 mg / PCS, with a moisture absorption ratio of 5.43%; and the saturated moisture absorption was 1183.7 mg / PCS, with a moisture absorption ratio of 13.39% (saturation is reached in 8 weeks). No surface exudates were observed during the test.

[0029] Example 2: Preparation of desiccant component sample S2. Following the formulation of MS(4A) 65%, PP 33.5%, and PEG 1.5%, the components were mixed and then melt-blended and extruded to obtain the sample S2. The structure of sample S2 was identical to that of sample S1. Sample S2 was subjected to moisture absorption tests at 25℃ / 50%RH and 25℃ / 90%RH environments, respectively.

[0030] Example 2 Test Results: At 25℃ / 50%RH, the 7-day moisture absorption was 202.2 mg / PCS, with a moisture absorption ratio of 2.27%. At 25℃ / 90%RH, the 24-hour moisture absorption was 230.5 mg / PCS, with a moisture absorption ratio of 2.59%; the 7-day moisture absorption was 700.6 mg / PCS, with a moisture absorption ratio of 7.87%; the saturated moisture absorption was 1465.9 mg / PCS, with a moisture absorption ratio of 16.47% (saturation was reached after 8 weeks). No surface exudates were observed during the test.

[0031] Example 3: Preparation of desiccant component sample S3. Following the formulation of MS(4A) 65%, PP 33%, and PEG 2%, the components were mixed and then melt-blended and extruded to obtain the sample S3. The structure of sample S3 was identical to that of sample S1. Sample S3 was subjected to moisture absorption tests at 25℃ / 50%RH and 25℃ / 90%RH environments, respectively.

[0032] Example 3 Test Results: At 25℃ / 50%RH, the 7-day moisture absorption was 212.8 mg / PCS, with a moisture absorption ratio of 2.34%. At 25℃ / 90%RH, the 24-hour moisture absorption was 262.3 mg / PCS, with a moisture absorption ratio of 2.88%; the 7-day moisture absorption was 786.3 mg / PCS, with a moisture absorption ratio of 8.64%; the saturated moisture absorption was 1449.6 mg / PCS, with a moisture absorption ratio of 15.93% (saturation was reached after 6 weeks). No surface exudates were observed during the test.

[0033] Example 4: Preparation of desiccant component sample S4. Following the formulation of MS(4A) 65%, PP 32.5%, and PEG 2.5%, the components were mixed and then melt-blended and extruded to obtain the sample S4. The structure of sample S4 was the same as that of sample S1. Sample S4 was subjected to moisture absorption tests at 25℃ / 50%RH and 25℃ / 90%RH environments, respectively.

[0034] Example 4 Test Results: At 25℃ / 50%RH, the moisture absorption after 7 days was 258.5 mg / PCS, with a moisture absorption ratio of 2.92%. At 25℃ / 90%RH, the moisture absorption after 24 hours was 272.2 mg / PCS, with a moisture absorption ratio of 3.07%; the moisture absorption after 7 days was 941.2 mg / PCS, with a moisture absorption ratio of 10.62%; and the moisture absorption after 14 days reached 1360.9 mg / PCS, with a moisture absorption ratio of 15.36%. Surface precipitates were observed, and the test was suspended; no saturation moisture absorption data was available. Analysis of the cause of precipitation: After PEG became saturated with water, moisture overflowed and carried away MS(4A) powder, resulting in grease-like precipitates on the surface of the desiccant component.

[0035] Example 5: Preparation of desiccant component sample S5. Following the formulation of MS(4A) 65%, PP 32%, and PEG 3%, the components were mixed and then melt-blended and extruded to obtain the sample S5. The structure of sample S5 is the same as that of sample S1. Sample S5 was subjected to moisture absorption tests at 25℃ / 50%RH and 25℃ / 90%RH environments, respectively.

[0036] Example 5 Test Results: At 25℃ / 50%RH, the moisture absorption after 7 days was 277.9 mg / PCS, with a moisture absorption ratio of 3.09%. At 25℃ / 90%RH, the moisture absorption after 24 hours was 333.3 mg / PCS, with a moisture absorption ratio of 3.71%; the moisture absorption after 7 days reached 1166.5 mg / PCS, with a moisture absorption ratio of 12.98%. Surface precipitates were observed, and the test was suspended.

[0037] Example 6: Preparation of desiccant component sample S6. Following the formulation of MS(4A) 65%, PP 31%, and PEG 4%, the components were mixed and then melt-blended and extruded to obtain the sample S6. The structure of sample S6 is the same as that of sample S1. Sample S6 was subjected to moisture absorption tests at 25℃ / 50%RH and 25℃ / 90%RH environments, respectively.

[0038] Example 6 Test Results: At 25℃ / 50%RH, the moisture absorption after 7 days was 434.8 mg / PCS, with a moisture absorption ratio of 4.44%. At 25℃ / 90%RH, the moisture absorption after 24 hours was 419.3 mg / PCS, with a moisture absorption ratio of 4.28%; the moisture absorption after 5 days reached 1193.9 mg / PCS, with a moisture absorption ratio of 12.20%, and surface precipitates were observed.

[0039] Example 7: Preparation of desiccant component sample S7. Following the formulation of MS(4A) 65%, PP 31%, and PEG 4%, the components were melt-blended. The structure of sample S7 differs from that of sample S1; sample S7 has a bottle-shaped (or cup-shaped) structure with an opening. Sample S7 may include a substrate and a desiccant layer. The substrate has the aforementioned bottle-shaped (or cup-shaped) structure, and the desiccant layer is formed on the inner wall of the substrate. Sample S7 can be formed using a two-color injection molding process. Specifically, the plastic substrate can be injection molded first, and then the aforementioned mixture can be injection molded onto the inner wall of the substrate to form the desiccant layer. Sample S7 was placed in an environment of 22°C / 80%RH for moisture absorption testing.

[0040] Example 7 Test Results: Under 22℃ / 80%RH conditions, the 24-hour moisture absorption was 252.9 mg / PCS, with a moisture absorption ratio of 0.65%; the 7-day moisture absorption was 721.5 mg / PCS, with a moisture absorption ratio of 1.87%; the saturated moisture absorption was 3121.76 mg / PCS, with a moisture absorption ratio of 8.08% (saturation was reached after 15 weeks). No surface exudates were observed during the test.

[0041] Comparative Example 1: Preparation of Comparative Sample C1. Sample C1 was prepared by mixing 65% MS(4A) molecular sieve and 35% polypropylene (PP), followed by melt blending and extrusion granulation. The structure of sample C1 is identical to that of sample S1. Sample C1 was subjected to moisture absorption tests at 25℃ / 50%RH and 25℃ / 90%RH. C1 corresponds to the binary system of "molecular sieve + binder" in the prior art.

[0042] Comparative Example 1 test results: Under 25℃ / 50%RH conditions, the 7-day moisture absorption was 124.8 mg / PCS, with a moisture absorption ratio of 1.32%. Under 25℃ / 90%RH conditions, the 24-hour moisture absorption was 137.2 mg / PCS, with a moisture absorption ratio of 1.45%; the 7-day moisture absorption was 323.5 mg / PCS, with a moisture absorption ratio of 3.42%; the saturated moisture absorption was 1091.7 mg / PCS, with a moisture absorption ratio of 11.54% (saturated after 13 weeks). Comparison of Sample C1 with Example 1 (Sample S1) demonstrates that adding hydrophilic polyether glycol to the same molecular sieve and polyolefin base can significantly improve the moisture absorption rate and moisture absorption.

[0043] The test results of Comparative Example 1 show that the binary system (C1) without hydrophilic polyether glycol has a moisture absorption of 323.5 mg / PCS after 7 days at 25°C / 90%RH, which is only 67.4% of that of Example 1 (S1, 479.8 mg / PCS) containing 1% polyethylene glycol under the same conditions. In terms of saturated moisture absorption, C1 has a saturated moisture absorption of 1091.7 mg / PCS, which is 92.2% of the saturated moisture absorption of S1 (1183.7 mg / PCS). This indicates that even with only 1% hydrophilic polyether glycol, the moisture absorption performance of the desiccant component is significantly better than the aforementioned binary system. With increasing proportion of hydrophilic polyether glycol, the increase in moisture absorption performance is more significant, but the risk of surface precipitates in high humidity environments also increases accordingly.

[0044] The test results of the above embodiments and comparative examples are summarized in Tables 1 to 3.

[0045] Table 1: Moisture absorption performance at 25℃ / 90%RH

[0046] Table 2: Moisture absorption performance at 22℃ / 80%RH

[0047] Table 3: Moisture absorption performance after 7 days at 25℃ / 50%RH

[0048] As can be seen from the above embodiments, comparative examples, and Tables 1 to 3: (1) As the content of polyethylene glycol (PEG) increased from 1% to 4%, the moisture absorption rate and moisture absorption of the desiccant component were significantly improved (the moisture absorption of 7 days at 25℃ / 90%RH increased from 479.8mg / PCS to 1166.5mg / PCS (sample S6 had no 7-day data because surface precipitates appeared after 5 days, but its 5-day moisture absorption reached 1193.9mg / PCS); the moisture absorption of 7 days at 25℃ / 50%RH increased from 159.7mg / PCS to 434.8mg / PCS), and both were better than the binary system comparative sample C1 without polyethylene glycol (PEG), which proved the technical contribution of polyethylene glycol (PEG) as a moisture absorption promoter; (2) Under high humidity conditions of 25℃ / 90%RH, samples with a polyethylene glycol (PEG) content of no more than 2% (S1~S3) did not show surface precipitates after reaching saturation moisture absorption. Samples with a polyethylene glycol (PEG) content of more than 2% (S4~S6) were suspended from testing after surface precipitates appeared (sample S4 on day 14, sample S5 on day 7, and sample S6 on day 5). (3) In an environment of 22℃ / 80%RH, the saturated moisture absorption ratio of sample S7 with a polyethylene glycol (PEG) content of 4% reached 8.08% (15 weeks saturation) and no surface precipitates were observed, indicating that the high polyethylene glycol (PEG) formulation is suitable for an environment not exceeding 80%RH. (4) In practical applications, the formulation can be selected according to the ambient humidity: when the relative humidity is no more than 80%RH, the formulation with polypropylene (PP) accounting for 31%~33% and polyethylene glycol (PEG) accounting for 2%~4% should be selected; when the relative humidity is 80%~90%RH, the formulation with polyolefin accounting for 33%~34% and PEG accounting for no more than 2% should be selected.

[0049] Furthermore, in practical applications, the selection of desiccant components must comprehensively consider factors such as the temperature and humidity range of the operating environment, sealing conditions, and the required drying time. For small device packaging with good sealing conditions, granular desiccant components can be selected to make full use of the limited packaging space; for food or pharmaceutical packaging with larger spaces, sheet-like or cylindrical desiccant components with three-dimensional structures can be selected to increase the moisture absorption area. In long-term storage scenarios, it is advisable to prioritize the selection of formulation types that match the humidity of the storage environment to ensure effective moisture absorption performance during the target storage period, while avoiding the impact of surface exudates on the quality of the protected product.

[0050] Based on the above results, the desiccant component of this application can be divided into two types according to the humidity of the operating environment: the first type (with a hydrophilic polyether diol content of no more than 2%) is suitable for high humidity environments of 80%~90%RH, and the second type (with a hydrophilic polyether diol content of 2%~4%) is suitable for environments with a humidity of no more than 80%RH, thus achieving optimal moisture absorption performance under different humidity conditions. Of course, the first type (with a hydrophilic polyether diol content of no more than 2%) can also be used in environments with a humidity of no more than 80%RH.

[0051] The above description is merely a preferred embodiment of this application and is not intended to limit the scope of protection of this application. For those skilled in the art, any improvements and modifications made without departing from the concept of this application, or equivalent substitutions and variations made based on the disclosure of this application, should be included within the scope of protection of this application.

Claims

1. A desiccant component, characterized in that, It includes type A zeolite molecular sieve, polyolefin and hydrophilic polyether glycol, of which, based on the total weight of the desiccant components, polyolefin accounts for 31% to 34% and hydrophilic polyether glycol accounts for 1% to 4%.

2. The desiccant component according to claim 1, characterized in that, The type A zeolite molecular sieve is selected from one or more of 4A molecular sieve, 3A molecular sieve, and 5A molecular sieve.

3. The desiccant component according to claim 2, characterized in that, The proportion of type A zeolite molecular sieve is 60% to 70%, preferably 65%.

4. The desiccant component according to any one of claims 1 to 3, characterized in that, The polyolefin is selected from one or more of polypropylene, high-density polyethylene, low-density polyethylene, and linear low-density polyethylene.

5. The desiccant component according to claim 4, characterized in that, The polyolefin is polypropylene.

6. The desiccant component according to any one of claims 1 to 5, characterized in that, The hydrophilic polyether diol is selected from one or more of polyethylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, and triethylene glycol.

7. The desiccant component according to claim 6, characterized in that, The hydrophilic polyether diol is polyethylene glycol.

8. The desiccant component according to any one of claims 1 to 7, characterized in that, The desiccant component is used in environments with a relative humidity not exceeding 80%RH, and the proportion of polyolefin is 31%~33%, while the proportion of hydrophilic polyether glycol is 2%~4%.

9. The desiccant component according to any one of claims 1 to 7, characterized in that, The desiccant component is used in environments with a relative humidity of 80% to 90% RH, and the proportion of polyolefin is 33% to 34%, while the proportion of hydrophilic polyether diol is 1% to 2%.

10. The desiccant component according to any one of claims 1 to 9, characterized in that, The desiccant component can be in the form of granules, flakes, or columns.

11. The desiccant component according to any one of claims 1 to 10, characterized in that, The desiccant component is made by mixing type A zeolite molecular sieve, polyolefin and hydrophilic polyether glycol in a certain proportion, followed by melt blending, and then extrusion granulation or injection molding.

12. The use of a desiccant component as described in any one of claims 1 to 11 in electronic device packaging, food packaging, or pharmaceutical packaging.